USING PICTURES TO IMPROVE STUDENTS’ ENGLISH VOCABULARY AT SEVENTH GRADE OF SMP NEGERI 1 SIAU TIMUR SELATAN - Vemi Wati Sabanari; Paula Rombepajung; Tirza Kumayas (Program Studi Pendidikan Bahasa Inggris, 2022)
This study was concerned the vocabulary teaching which aims at determining whether or not students’ English vocabulary can be improved by using pictures. The subjects of this study consisted of 21 students at the seventh grade of SMP Negeri 1 Siau Timur Selatan. The writer used the quantitative method in analyzing while the data was collected through pretest and posttest. The writer used the mean score formula in analyzing the data. The type of test that would be given to students was multiple choice with a total fo 20 questions. The students are taught using pictures and there was about things in the classroom. Results of this study indicated a significant improvement in students' English vocabulary after using media in the form of pictures in teaching vocabulary. This can be proven by the average value of the pretest was 3.67 while the posttest was 7.81. It means that pictures is effectively considered to be used in improving students' English vocabulary.